1997
DOI: 10.1359/jbmr.1997.12.10.1596
|View full text |Cite
|
Sign up to set email alerts
|

The Mitogenic Effect of Parathyroid Hormone Is Associated with E2F-Dependent Activation of Cyclin-Dependent Kinase 1 (cdc2) in Osteoblast Precursors

Abstract: Injections of parathyroid hormone (PTH) have been reported to stimulate skeletal accretion through increased bone formation in several species, and osteoblast proliferation is a critical component of bone formation. However, the biological mechanisms of PTH-stimulated bone cell proliferation are largely unknown. In this study, we demonstrated that PTH stimulates proliferation of the osteoblast precursor cell line, TE-85, in association with increasing cdc2 protein levels and its kinase activity. cdc2 antisense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Uremic bone is resistant to the actions of PTH (13), defined as release of calcium from the skeleton after a dose of PTH, and a certain amount of hyperparathyroidism is required to maintain bone turnover. However, PTH is a poor director of osteoblast differentiation in vitro (17,21,69), and excess PTH ultimately leads to accumulation of fibrous cells in trabecular bone (21) and elevated rates of bone formation but excess bone resorption (i.e. high turnover renal osteodystrophy).…”
Section: Discussionmentioning
confidence: 99%
“…Uremic bone is resistant to the actions of PTH (13), defined as release of calcium from the skeleton after a dose of PTH, and a certain amount of hyperparathyroidism is required to maintain bone turnover. However, PTH is a poor director of osteoblast differentiation in vitro (17,21,69), and excess PTH ultimately leads to accumulation of fibrous cells in trabecular bone (21) and elevated rates of bone formation but excess bone resorption (i.e. high turnover renal osteodystrophy).…”
Section: Discussionmentioning
confidence: 99%
“…Since T antigen is a powerful mitogen with multiple growth-inducing activities, it is possible that the J domain is required to drive the cells to cycle in a manner that indirectly disrupts pRB-E2F complexes. For example, several different mitogens will induce free E2F and transcriptional activity even though they are not known to directly bind to the pRB family (83,92,169,258). Biochemical evidence, however, clearly demonstrates that T antigen has the capability to disrupt pRB-E2F family complexes in vitro (233).…”
Section: Role Of J Domain In Prb Complexesmentioning
confidence: 99%
“…Previous in vivo and in vitro studies have suggested that PTH can stimulate the replication of osteoblast progenitors (41)(42)(43). However, the equivalent anabolic response of normal SAMR1 and SAMP6 mice with defective osteoblastogenesis to daily injections of hPTH , together with the failure to observe a stimulatory effect of the hormone on the number of osteoblast progenitors obtained from the marrow of either strain, strongly suggests that the anabolic effect of PTH is not dependent on increased osteoblastogenesis.…”
mentioning
confidence: 95%